The Relationship of Religiosity towards Students’ Perceived Teacher Management Skills and Its Implications for Guidance and Counseling Practice - Mispani; Aprezo Pardodi Maba (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The present study aimed to examine the relationship between religiosity and students' perceived teacher management skills, and to explore the implications of this relationship for guidance and counseling practice. A sample of 102 participants was collected from a specific population and cultural context, and religiosity and perceived teacher management skills were measured using adapted and validated scales. Results of a regression analysis showed that there is a weak but statistically significant relationship between religiosity and perceived teacher management skills, with religiosity explaining a small percentage of the variance in perceived teacher management skills. These findings suggest that religiosity may play a small role in shaping students' perceptions of their teachers' management skills, but it is not the only factor. Overall, the study suggests that guidance and counseling practice should consider other factors such as the teachers' personal characteristics, teaching methods and environmental factors when working with teachers. It would beneficial to make an effective teaching for the teacher and learning for the students. Keywords: Teacher Management Skills, Students' Perceptions, Guidance and Counseling Practice